Menakar Konstitusionalitas Kebijakan Redistribusi Tanah untuk Lahan Pertanian dalam UU No. 19 Tahun 2013 - Wildan Humaidi (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2018)
Land redistribution is government policy to implement Article 33 Paragraph (3) of the 1945 Constitution, where the people is the holders of authority over the earth, the water and the other natural resources of Indonesia. In fact, the land redistribution in Law No. 19 of 2013 about the Farmers Protection and Empowerment, specifically Article 59 which states "convenience for Farmers to obtain Agricultural land as referred to in Article 58 paragraph (3) point a given in the form of leasing rights, concession permits, management permits, or utilization permits", considered to have violated the constitution. Through judicial review, the Court has issued Decision No. 87 / PUU-XI / 2013 and consider the phrase "leasing rights" to be contrary to the 1945 Constitution. This article attempts to elaborate two main problems; the form of government policy about land redistribution for agricultural land inthe Law Number 19 of 2013 about the Farmers Protection and Empowerment and the constitutionality of state land redistribution for agriculture in the Constitutional Court Decision No. 87 / PUU-XI / 2013.